The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/pat.117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neat resins based on methacrylates modified with methacryl‐POSS, as potential organic–Inorganic hybrids for formulating dental restoratives

Abstract: Three series of neat resins, based on methacrylates or dimethacrylates modified with 1‐[3‐(methacryl)propyl]‐3,5,7,9,11,13,15‐heptacyclopentylpentacyclo[9.5.113,­9.15,15.17,13]octasiloxane (Methacryl‐POSS or POSS‐MA), were evaluated. Incorporation of POSS‐MA into the polymeric matrix was accomplished in three ways: (a) resins series I was formulated with one‐pot copolymerization of a bis‐GMA/diluent monomer with POSS‐MA; (b) the copolymer of 2‐hydroxylethyl methacrylate (HEMA) and POSS‐MA, with a weight ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 5 publications
3
48
0
Order By: Relevance
“…It is assumed that siloxane network is so hard that it even does not change at this temperature. Nevertheless, pore size is expectable and comparable with domain sizes of a polymer in the initial hybrid, which confirms its dendrimer structure [77]. If the first group of monomers for producing nanocomposites by sol-gel synthesis includes compounds tending to opening of a multiple bond, the second one no less widely spread, includes polymerization transformations of compositions like (RO) 3 M-X-A, in which X is a connecting bridge (organic spacer), and A-group is able to be subjected to opening of the cycle, polymerization (polycondensation) or coupling reaction [28].…”
Section: Combination Of Reactions Of Polymerization and Sol-gel Synthsupporting
confidence: 71%
See 1 more Smart Citation
“…It is assumed that siloxane network is so hard that it even does not change at this temperature. Nevertheless, pore size is expectable and comparable with domain sizes of a polymer in the initial hybrid, which confirms its dendrimer structure [77]. If the first group of monomers for producing nanocomposites by sol-gel synthesis includes compounds tending to opening of a multiple bond, the second one no less widely spread, includes polymerization transformations of compositions like (RO) 3 M-X-A, in which X is a connecting bridge (organic spacer), and A-group is able to be subjected to opening of the cycle, polymerization (polycondensation) or coupling reaction [28].…”
Section: Combination Of Reactions Of Polymerization and Sol-gel Synthsupporting
confidence: 71%
“…4.6). These products are promising as potential alternative for usage in dental prosthetics, because the materials based on multi-methacrylates have low shrinking deformation 4 [77]. Really, including of just 5 wt% of POSS-MA almost restores shrinking of standard materials.…”
Section: Combination Of Reactions Of Polymerization and Sol-gel Synthmentioning
confidence: 98%
“…Their work indicated that synthesising POSS-containing macromonomers enabled the improved overall dispersibility of POSS when reacted with dental monomers. [96,97] Methacrylated and octaphenyl-POSS moieties have been reacted with HEMA (2-hydroxyethylmethacrylate), BisGMA (bis-phenol A-glycidyldimethacrylate), and TEGDMA (tetraethylglycidylmethacrylate)-based restorative fillers, and Dodiuk-Kenig et al compared the effect of the two different terminal functional groups on POSS by investigating the thermal, mechanical, and physical properties. They found that acrylated POSS resulted in a 5 8C increase in T g , a 7% increase in compressive strength, an increase in bond shear strength (36%), and a decrease in polymer shrinkage by 28%, while incorporation of octaphenyl-POSS decreased the compressive strength by 20%, the bond shear strength by 49%, and polymer shrinkage by 67%.…”
Section: Wwwmaterialsviewscommentioning
confidence: 99%
“…Moreover, an increased T g and oxygen permeability have been demonstrated when POSS derivatives are incorporated into polymer matrices. [94,96,97] In a study by Culbertson et al three different methods of incorporating a mono-methacrylated POSS into dental composites were studied as follows: 1) by manufacturing POSS-containing macromonomers, and copolymerization with dental monomers, 2) by using a one step polymerisation of POSS with dental monomers, and 3) by developing a POSS co-polymer followed by in situ polymerisation with dental monomers. The results demonstrated that reacting methacrylate POSS into known dental polymeric formulations significantly decreased polymer shrinkage, although a slight reduction in mechanical properties was observed, especially at loadings greater than 10 wt.-%.…”
Section: Wwwmaterialsviewscommentioning
confidence: 99%
See 1 more Smart Citation